The effect of students' effort–reward imbalance on learning engagement: the mediating role of learned helplessness and the moderating role of social support - Liu, Shengmin; Wang, Yuanru; He, Wanning; Chen, Yu; Wang, Qiangqiang (Frontiers in Psychology, 2024)
Introduction To explore the predictive effect of effort–reward imbalance on students' learning engagement and to elucidate the underlying mechanism, 796 students were selected for a survey. Methods The participants were required to complete four scales: the Effort-reward Imbalance Scale, the Learning Engagement Scale, the Learned Helplessness Questionnaire, and the Perceived Social Support Scale. Results (1) Students' effort–reward imbalance significantly and negatively predicts their learning engagement; (2) Learned helplessness serves as a mediator in the relationship between students' effort–reward imbalance and learning engagement; (3) Social support plays a moderating role in the association between effort–reward imbalance and learned helplessness. High levels of social support can buffer the impact of an effort–reward imbalance on learned helplessness, and the protective effect of social support is more obvious when the effort–reward imbalance is low. Discussion The present study revealed how an effort–reward imbalance affects learning engagement among students through the dimensions of learned helplessness and perceived social support. The constructed model not only further clarifies the mechanism underlying the relationship between effort–reward imbalance and learning engagement but also holds significant implications for guiding students' education.